Serum concentrations of IL-16 and its genetic polymorphism rs4778889 affect the susceptibility and severity of endometriosis in Nigerian women - Ochuwa Adiketu Babah; Oyesola Oyewole Ojewunmi; Chika Kingsley Onwuamah; Ifeoma Christiana Udenze; Akinniyi Adediran Osuntoki; Bosede Bukola Afolabi (BMC, 2023)
Abstract Background Endometriosis is the presence of active ectopic endometrial glands and stroma at other sites outside the uterine cavity. It is a common cause of chronic pelvic pain which is sometimes debilitating, and inflammation is one of the known triggers of endometriosis. Interleukins 6 and 16 (IL-6 and IL-16) are proinflammatory cytokines which play essential roles in inflammatory diseases. We therefore investigated the relationship between genetic polymorphisms of interleukins 6 and 16, and the development of endometriosis in Nigerian women. Method One hundred and thirty (130) consenting women were consecutively enrolled, sixty-five (65) of whom had endometriosis and 65 age-matched women as reference group, surgically confirmed as not having endometriosis. Spectrophotometric determination of serum concentrations of Interleukins 6 and 16 was carried out and the genotyping of IL-6 (rs1800795) and IL-16 (rs4778889, rs11556218, rs4072111) genes were performed using TaqMan assays. Results Serum IL-16 concentration was significantly higher in women with severe chronic pelvic pain compared to those with mild pain (p = 0.023). The C allele of rs4778889 was associated with endometriosis (OR: 1.80, 95% CI: 1.08 - 3.02, p = 0.024). Conclusion Serum IL-16 and IL-16 rs4778889 may be important markers for endometriosis in Nigerian, and by extension, African women. Multicentre African studies would clarify this.